LEXICAL VARIATION OF MADURESE SPOKEN IN BANGKALAN, MADURA - Dona Rahayu Sugiharti; Pariyanto Pariyanto (Universitas 17 Agustus 1945 Surabaya, 2021)
Madurese is the language used by the Madurese ethnic community, both living on the island of Madura and outside the island as a social language. The Madurese language has several dialects, but in a dialect, there are also several variations found in one area, for example, Bangkalan Regency. The purpose of this study is to obtain an overview of the variations of the Madurese lexicon in the Bangkalan Regency and to determine the isolect status of the different lexicon in the Bangkalan Regency. This study uses 335 glosses which are divided into 12 meaning fields to collect data in the field. Three informants for each research area (DP) were employed and dialectometric calculations were used to determine isolect status. The results showed that there were 216 differences in the lexicon from 335 glosses. Dialectometry analysis of lexical differences in DP 2: DP 4, DP 3: DP 4, and DP 4: DP 1 were 95.37%, 89.35%, and 90.74% respectively, suggesting that the lexical variations were used in DP 4. The percentage of the three other comparison areas shows under 20%, indicating there is no difference. In short, lexical variations of Madurese exists mostly in the Bangkalan Regency.